A novel digital watermarking scheme for data authentication and copyright protection in 5G networks. (November 2018) - Sk, Ayesha; Masilamani, V.
Abstract: The next generation wireless technology 5G is aimed at achieving very high data rates. Data authentication (DA) and ownership authentication (OA) are not considered in the previous telecommunication technologies. So, a framework for 5G wireless technology is proposed for DA and OA using watermarking in this article. These two applications (DA and OA) have conflicting features as the watermark needs to be fragile for DA and robust for OA. In the proposed scheme this conflicting issue has been addressed using a single watermark, unlike the existing schemes that use two watermarks. The novelty of this scheme is the instability property of Playfair cipher is used to achieve DA and OA. Our proposed method also provides a solution to the flaw (false positive problem) in singular value decomposition based watermarking. The proposed scheme is tested using the images from the standard datasets and the performance looks promising.